ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR TINGKAT RASIO LIKUIDITAS DAN PROFITABILITAS (Studi Pada PT Mayora Indah TBK Bengkulu) - Herlina Herlina; Asmawi Mangku Alam; Septi Nurindah Sari (JURNAL LENTERA AKUNTANSI, 2022)
This study aims to determine the condition of the financial statements, the calculation of the liquidity and profitability ratios, as well as the results of the analysis of the liquidity and profitability level ratios at PT Mayora Indah Tbk in 2019, 2020 and 2021. The methods used by the author in obtaining data are literature study methods and methods. observation. The results of the study concluded that the condition of the financial statements using horizontal comparative analysis was in good condition because each year it had increased. From the calculation of the liquidity ratio as measured by the current ratio and quick ratio method, it has increased and can be said to be liquid or above the industry average, so that the company is able to meet its short-term obligations (debt), but for the cash ratio method itself it is still said to be liquid. although the resulting ratios are above the industry average. This means that the company's ability to meet its short-term obligations (debt) is still not sufficient, but if the ratio results are compared with the industry average, it is quite good. From the calculation of profitability as measured by the return on assets method, return on equity and net profit margin are still not good because they are still below the industry average, even though the company has experienced an increase in profit, the company is still unable to manage the invested capital efficiently. Keywords: Financial Statement Analysis, Liquidity Ratio, Profitability